Democratic Republic of Congo - The Impact of the 'Decoupage' : Executive Summary - World Bank (World Bank, 2012)
In its new Constitution, proclaimed on February 18, 2006, the Democratic Republic of the Congo (DRC) committed itself to reforming its administrative and territorial architecture. Following this reform, the country, which now has 11 provinces, will be subdivided into 26 provinces. According to constitutional provisions, the transition from 11 to 26 provinces is to take place within three years after the establishment of the third Republic's main governing institutions. The Senate, the final institution to be established, was set up in May 2007, and the country's new administrative structure should be implemented by May 2010 at the latest. The aim of this study, which was carried out at the request of the Government of the DRC and jointly financed by the World Bank, the Belgian Development Cooperation, the European Commission, and the United Nations Development Program (UNDP), is an in depth analysis of the main aspects of the decoupage process. It includes an assessment of the administrative and institutional capacity of the new provinces and an examination of their financial and budgetary sustainability as well as of the economics of the process. The results of the study were presented to a validation workshop held in Kinshasa on July 16, 2008. The workshop was organized by the Government of the DRC, and it was attended by representatives of the President of the Republic, the Prime Minister, the National Assembly, the Senate, the Ministries of Decentralization, finance, budgeting, and planning, representatives from the various provinces involved in the decoupage process, and development partners including the World Bank, UNDP, the Belgian Development Cooperation, and the European Union. At the end of the workshop, recommendations for rationalizing the decoupage process in the DRC were made with a view to maximizing efficiency. These recommendations are listed at the end of each chapter in this study.